On music production in mathematics teacher education as an aesthetic experience - da Silva, Ricardo Scucuglia Rodrigues [UNESP] (Springer Nature, 2020)
This paper addresses the integrated use of the arts and digital technology in mathematics education—specifically involving aspects of preservice teachers’ mathematical activity while engaging in music production, in pedagogic scenarios conceived of as aesthetic mathematical experiences (AMEs). Theoretically, the research evokes notions such as digital mathematical performance, aesthetics, humans-with-media, and musical theory. Methodologically, the study presents a pedagogic model for mathematics teaching and learning through music production; the model is elaborated using qualitative case studies in which preservice teachers (education majors and mathematics majors) created mathematical songs with music software. In their songs, the education majors explored place value and the mathematics majors explored progressions. The research highlights the mathematical ideas and the narrative nature of the lyrics, as well as the digital structure of the songs created collectively. The study also emphasizes aspects of thinking-with-music-software related to musical concepts such as intervals, note values, and harmonic fields. The results reveal that the AMEs offered ways for preservice teachers to think mathematically and aesthetically through the composition of the lyrics and by the creation of virtual instruments with music software.
Keywords: Aesthetics; Digital technology; Mathematical songs; Music software